Evaluation of Continuous Emission Monitoring System (CEMS) Performance and Integration with Data Acquisition and Interfacing Systems for Regulatory Compliance in Indonesia's Industrial Sector - Herawan, Hery (Asosiasi Dosen Muda Indonesia, 2026)
Air pollution from industrial emissions is a critical issue in Indonesia, affecting public health and the environment. Continuous Emission Monitoring Systems (CEMS) are crucial for real-time monitoring and ensuring compliance with environmental regulations. Objective: This study aims to evaluate the performance of the CEMS integrated with the Data Acquisition System (DAS) and Data Interfacing System (DIS), developed by BRIN and PT Eksperta Adi Manusa, to improve emissions monitoring and reporting. Methodology: A case study evaluation with a descriptive-qualitative and observational approach was used. Data was collected through simulations with MODBUS data, system documentation analysis, and performance testing of the dashboard module. The study focused on system architecture, data integration, and compliance with Indonesian environmental regulations. Findings: The integration of CEMS with DAS and DIS successfully enabled real-time monitoring and enhanced emission data accuracy. However, challenges such as data variability and the need for stronger regulatory supervision were identified. The research also found that predictive emission monitoring systems (PEMS) could improve system performance and reduce operational costs. Implications: This research contributes to improving air quality management in Indonesia. The findings highlight the importance of real-time monitoring and system integration for better decision-making and regulatory compliance. The study provides recommendations for policymakers and industry stakeholders to optimize CEMS and PEMS implementation for reducing industrial pollution. Originality: This research provides original insights into CEMS integration within Indonesia’s regulatory framework, a relatively unexplored area. It contributes to the field of environmental monitoring by offering practical recommendations to enhance emission monitoring systems and address challenges faced by industries in complying with regulations.